Influence of residual stress on the stability of steel columns at elevated temperatures - Kervalishvili, Andrei; Talvik, Ivar (Journal of Civil Engineering and Management, 2017)
Influence of residual stresses on the stability of steel columns with various sections at elevated temperatures has been studied. The potential effect of residual stresses on the stability of columns should be clarified, as the stability of compression elements in fire even without explicitly regarding residual stresses is not a straightforward phenomenon. Extensive numerical study was performed utilizing non-linear finite element method. Results for models ignoring and accounting for residual stresses were compared for different steel grades, various slenderness values, temperatures and section types. Results were compared with Eurocode method.